2014
DOI: 10.1177/1550059413509616
|View full text |Cite
|
Sign up to set email alerts
|

Automated Analysis of Background EEG and Reactivity During Therapeutic Hypothermia in Comatose Patients After Cardiac Arrest

Abstract: Visual analysis of EEG background and reactivity during therapeutic hypothermia provides important outcome information, but is time-consuming and not always consistent between reviewers. An automated EEG analysis approach may help to quantify the brain damage. Fortysix comatose patients in therapeutic hypothermia after cardiac arrest were included in the study. EEG background was quantified with burst-suppression ratio and approximate entropy, both used to monitor anesthesia. Reactivity was detected through ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
65
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

6
4

Authors

Journals

citations
Cited by 89 publications
(69 citation statements)
references
References 30 publications
1
65
1
2
Order By: Relevance
“…Considering the delicacy in reliably deciding upon a voltage amplitude around 20 lV in some patients [7], other groups concentrated rather on background reactivity to stimuli, which if present during TH has been reported to herald good prognosis in as much as 86 % [8], while lack of reactivity portended a poor prognosis in a much higher rate (99 % in [9]). This last figure contrasts with a predictive value of 86 % in this study (it was, however, not indicated when reactivity was assessed), pinpointing the lack of standardization of its testing (in this series with auditory and peripheral painful stimuli; in the aforementioned papers applying also vigorous pressure to the nipples) and its scoring [7,10]. In the same context, identical bursts, recently reported to perfectly correlate with poor outcome [11], in this study show an overlapping significance with that of suppression-burst; the authors postulate that use of midazolam versus propofol might generate different burst types, and that those induced by propofol might be compatible with good outcome.…”
contrasting
confidence: 47%
“…Considering the delicacy in reliably deciding upon a voltage amplitude around 20 lV in some patients [7], other groups concentrated rather on background reactivity to stimuli, which if present during TH has been reported to herald good prognosis in as much as 86 % [8], while lack of reactivity portended a poor prognosis in a much higher rate (99 % in [9]). This last figure contrasts with a predictive value of 86 % in this study (it was, however, not indicated when reactivity was assessed), pinpointing the lack of standardization of its testing (in this series with auditory and peripheral painful stimuli; in the aforementioned papers applying also vigorous pressure to the nipples) and its scoring [7,10]. In the same context, identical bursts, recently reported to perfectly correlate with poor outcome [11], in this study show an overlapping significance with that of suppression-burst; the authors postulate that use of midazolam versus propofol might generate different burst types, and that those induced by propofol might be compatible with good outcome.…”
contrasting
confidence: 47%
“…Reactivity has been used relatively widely as a prognostic tool in comatose patients [4][5][6][7][8][9][10] and recent studies show divergent interrater agreements 17,18 ; it is crucial to test it in a reproducible manner to minimize false negative interpretations, which may have potentially devastating consequences. Nipples are rich in sensory receptors innervated by lateral and anterior cutaneous branches of the 3rd, 4th, and 5th intercostal nerves 19 ;…”
Section: Discussionmentioning
confidence: 99%
“…In particular, automated algorithms have been developed to reduce the subjective part of EEG interpretation (Noirhomme et al, 2014), but are still very far from routine clinical use. More advanced analyses, including single-trial topographic interpretation applied to mismatch negativity paradigms (Tzovara et al, 2013) or comparison of small-world characteristics of EEG spontaneous activity (Beudel et al, 2014) are showing promising results in outcome prediction, but, again, these are still the subject of scientific research and are not (yet) ready for clinical application.…”
Section: Perspectivesmentioning
confidence: 99%